AB1127-HPR Construct Validity Testing of Rast, A New RA Stiffness Patient Reported Outcome Measure (PROM). (15th July 2016) - Halls, S.; Dures, E.; Kirwan, J.; Pollock, J.; Baker, G.; Edmunds, A.; Hewlett, S.
Abstract : Background: Morning stiffness is a frequently used clinical and research outcome measure and is important to patients 1, but was omitted from the RA core set because of poor measurement properties 2 . Current stiffness assessment is inconsistent with patient's perspectives of the symptom 3, 4 and has not been developed according to PROM development guidelines 5 . A new 21 item, 3-component Rheumatoid Arthritis Stiffness questionnaire (RAST) has been developed based on qualitative work 3 with RA patients and statistical assessment to enhance content validity and now requires testing for appropriate relationships with other measures of disease (construct validity). Objectives: To perform construct validity testing of RAST. Methods: The 21 item RAST was developed from 45 items assessing stiffness included in a questionnaire pack which was posted to patients with RA based in the South-West of England. The questionnaire pack also contained individual items capturing pain (VAS), fatigue (NRS), patient global assessment (PtG VAS), questionnaires capturing disability (MHAQ), and patient-reported disease activity (PDAS2 6, scores generated from an algorithm including PtG, swollen joint count (SJC), and MHAQ), and basic demographic information. The RAST was subjected to construct validity testing using a correlation matrix of Spearman's correlation coefficients (reported as explained variance (R 2 ). Results: 277 patients (91 male) aged 23–97 years with disease durations 1–45 years participated in the study (42.9% response rate). The individual components and sum score of RAST demonstrated appropriate relationships with other measures of disease (pain R 2 =45–72%; fatigue R 2 =43–55%; PtG R 2 =48–68%; MHAQ R 2 =55–78%; PDAS2 6 R 2 =56–78%). The shared variance indicated that while RAST (individual components and sum score) is related to other measures of disease, it is not measuring the same thing. Importantly, as identified by patients in earlier qualitative work 3, the variance explained by the RAST (individual components and sum score) and the (patient-reported) SJC included within the PDAS2 6 was between 31–41% indicating that RAST may capture something not currently included within disease activity assessment. The pattern of relationships between individual components and measures of disease also provided support for the 3-component structure. As expected, the "physical component" shared the most variance with disability (R 2 =78%), the "severity component" shared the most variance with pain (R 2 =72%) and PtG (R 2 =68%), and the "psychosocial component" shared less variance with the above disease related measures. Conclusions: During preliminary validity testing RAST, the new RA stiffness PROM, demonstrated promising construct validity. Further testing of RAST is now required in a fresh population to generate measurement property evidence of reliability and sensitivity to change to support its use. References: Hewlett et al, 2005; Felson et al, 1993; Halls et al, 2014; Orbai et al, 2014; FDA, 2009; Choy et al, 2008; 2015 Disclosure of Interest: None declared